Temperature comparison of different reflective surfaces of a solar thermal collector - Koh Y.Y.; Chua Y.L.; Chin K.K. (American Institute of Physics Inc., 2023)
With the rapid depletion of fossil fuels, the search for application of alternative energy sources becomes more important than ever before. Solar energy has been identified as one of the major renewable energy that will contribute to power generation is years to come. There are two major categories of solar energy applications. Solar thermal collector is one of it. This paper presents an investigation on the effect of different reflecting surfaces on solar thermal collector. Three different reflective surfaces were applied on the surface of the solar thermal collector. Data was collected and analyzed. From the results, the aluminum mirror sheet performed best. 2017 Author(s).